MINAPOLITAN PROGRAM AND ITS ROLE IN THE DEVELOPMENT OF CAPTURE FISHERIES IN EAST ACEH REGENCY - Jamilah, Jamilah; Mawardati, Mawardati (Jurnal Aplikasi Manajemen, 2018)
This research is aimed at analyzing the minapolitan program and its role in the development of capture fisheries in East Aceh Regency. The method used in this study was survey method. The Regency, namely East Aceh Regency, was determined purposively as capture fisheries minapolitan area based on the Decree of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia Number 35/ KEPMEN-KP/ 2013. The analysis of the role of minapolitan programs in the development of capture fisheries of East Aceh Regency includes the achievements and obstacles faced in the implementation of the minapolitan program in East Aceh Regency using qualitative and quantitative descriptive approach.The results show that the capture fishery in East Aceh Regency is potential to be developed because it is located in Indonesia-Malaysia-Thailand Growth Triangle (IMTGT), fishery resources and infrastructure are available, and export market opportunities of fishery products are open wide. The lack of fish processing encourages local governments to improve Fish Processing Units (UPI). Minapolitan Area Development Program in East Aceh Regency has a positive impact on capture fisheries, such as improving infrastructures in minapolitan area, increasing the production of capture fisheries in minapolitan area, employment absorption, and fishing infrastructure, increasing capture fisheries, improving the quality and quantity of human resources (HR), and increasing capital and investment. This program needs to be done continuously to develop sustainable capture fisheries in East Aceh Regency.